2012
DOI: 10.1016/j.jamcollsurg.2011.10.015
|View full text |Cite
|
Sign up to set email alerts
|

Violation of the Rectus Complex Is Not a Contraindication to Component Separation for Abdominal Wall Reconstruction

Abstract: Background Component separation (CS) is an effective technique for reconstructing complex abdominal wall defects. Violation of the rectus abdominis complex is considered a contraindication for CS, but we hypothesized that patients have similar outcomes with or without rectus complex violation. Study Design We retrospectively studied all consecutive patients who underwent CS for abdominal wall reconstruction over 8 years and compared outcomes of patients with and without rectus violation. Primary outcome meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69]. Components separation surgical outcomes were similar whether or not the rectus complex was violated [70]. Analytic morphomics can be used to compare preand post-operative changes in patients undergoing CS.…”
Section: Components Separationmentioning
confidence: 99%
See 1 more Smart Citation
“…The method can be performed in principal laparoscopically, too [66][67][68] and with advantages in obese patients [69]. Components separation surgical outcomes were similar whether or not the rectus complex was violated [70]. Analytic morphomics can be used to compare preand post-operative changes in patients undergoing CS.…”
Section: Components Separationmentioning
confidence: 99%
“…The technique can also be used in a violated rectus complex [70]. In very complex hernias, however, with increasing destruction of the original fascial situation (re-recurrence, much scarring, florid infection etc.…”
Section: Components Separationmentioning
confidence: 99%
“…These findings agree with previously published literature from our group and others, demonstrating that patients who undergo abdominal laparotomies classified as "clean" experience fewer reoperations and early, wound-related complications. 12, [15][16][17][18] More specifically, the AWR+O group experienced more infectious events, including subcutaneous abscess, deep infection, organ site infection, and >30 day SSI. However, we did not find that these infectious complications led to later ventral hernia recurrences.…”
Section: Discussionmentioning
confidence: 99%
“…The explanation for this finding may be related to the experience of our surgeons with complex abdominal wall reconstruction, our surgeons' adherence to key surgical principles (gentle handling of the soft tissue, minimal tension on the repair, minimal disruption to soft tissue vascularity), and the frequent use of ADM. ADM has been shown to maintain durability and functionality even in the repair of contaminated wounds. [15][16][17][18] Furthermore, it is less strongly associated with adhesion formation or the development of enterocutaneous fistulae compared to synthetic mesh. 20,21 Timmermans and colleagues 4 found that the presence of a parastomal hernia is associated with a 7-fold greater risk of developing a ventral incisional hernia.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical techniques in AWR have been previously described. [15, 18] Surgical site occurrence (SSO) was defined as any complication involving the abdominal wall. Wound dehiscence was defined as a skin breakdown with full-thickness skin separation extending over 2-cm with or without infection, while skin necrosis involved clearly demarcated necrotic skin edges over 1-cm in width.…”
Section: Methodsmentioning
confidence: 99%